Morphometric analysis of the sympatric species of the Crassiphycus corneus-C. usneoides complex (Gracilariaceae, Rhodophyta) of the Mexican coasts of the Gulf of Mexico and the Caribbean Sea - Vilchis, Martha Isabel; Dreckmann, Kurt M.; Quintanar-Isaías, Alejandra; Sentíes, Abel (Instituto de Ecología, A.C., 2020)
Background and Aims: Crassiphycus corneus and C. usneoides form a morphological complex of macroalgal species due to the overlap in the characters that delimit them. Given their low phenotypic plasticity and sympatric distribution, discrimination between both species is complicated. Therefore, the aim of this study was to morphometrically evaluate some anatomical characters that allow discrimination of species within the complex. Methods: With the 24 quantitative measurements obtained from 40 specimens of Crassiphycus corneus and C. usneoides, a principal component analysis was performed to determine whether there was morphometric discrimination between the species. The result of this analysis was evaluated by a NP-MANOVA. The arithmetic means and confidence intervals of the characters with the greatest weight in discrimination were represented in a graphic. In addition, a cluster analysis was performed to better support the previous analysis. Key results: The principal components analysis showed 24 components, of which the first three explain 88.6% of the variance. This analysis and the NP-MANOVA showed that the characters that differentiate both species are the largest diameter of the thallus in the medium portion and the largest and smallest diameter of the thallus in the apical portion, which, according to the arithmetic mean, are significantly larger in Crassiphycus usneoides compared to C. corneus. Cluster analysis based on the Euclidean distance and the UPGMA algorithm strengthened the previous analyses, confirming the presence of two groups (C. corneus and C. usneoides). Conclusions: The performed morphometric analysis proved efficient for the segregation of the species of the complex, and may serve as a reference point for the taxonomic delimitation of other cryptic macroalgal species.